2020
DOI: 10.1016/j.bbi.2020.04.049
|View full text |Cite
|
Sign up to set email alerts
|

A multinational, multicentre study on the psychological outcomes and associated physical symptoms amongst healthcare workers during COVID-19 outbreak

Abstract: Objective: Since the declaration of the coronavirus 2019 (COVID-19) outbreak as pandemic, there are reports on the increased prevalence of physical symptoms observed in the general population. We investigated the association between psychological outcomes and physical symptoms among healthcare workers. Methods: Healthcare workers from 5 major hospitals, involved in the care for COVID-19 patients, in Singapore and India were invited to participate in a study by performing a self-administered questionnaire withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

134
1,436
49
97

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,429 publications
(1,716 citation statements)
references
References 25 publications
134
1,436
49
97
Order By: Relevance
“…Sleep is an important time for the recuperation and rejuvenation of the brain. Unfortunately, a substantial body literature showed stressful life events and outbreaks of infectious disease including COVID-19 can affect the sleep quality [21,[26][27][28][29], 84.69% of the participants in our study with the poor sleep quality demonstrate it again. Using the correlation analysis, we also found levels of anxiety symptoms are associate with sleep quality in COVID-19 patients admitted to shelter Fangcang hospital.…”
Section: Discussionmentioning
confidence: 62%
“…Sleep is an important time for the recuperation and rejuvenation of the brain. Unfortunately, a substantial body literature showed stressful life events and outbreaks of infectious disease including COVID-19 can affect the sleep quality [21,[26][27][28][29], 84.69% of the participants in our study with the poor sleep quality demonstrate it again. Using the correlation analysis, we also found levels of anxiety symptoms are associate with sleep quality in COVID-19 patients admitted to shelter Fangcang hospital.…”
Section: Discussionmentioning
confidence: 62%
“…Although such measures have sdemonstrated their effectiveness, for optimal public health as well as economic outcomes, further investigation into their implementation within specific contextual factors should be prioritized. 46 Moreover, continued medical training for healthcare workers 47 and preventive measures for the workforce, 48 is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 99%
“…Moghanibashi-Mansourieh (2020),10 in applying an online questionnaire to 10,754 participants, found that the level of severe anxiety was serious for 9.3% of the participants and very serious for 9.8%. Chew et al (2020),28 conducting research among health professionals (n = 906), found that 8.7% (n = 79) of participants suffered from moderate to extremely severe anxiety, while Ahmed et al (2020)30 found a higher anxiety rate (29%), dangerous, harmful alcohol consumption or alcohol dependence (30%), and lower than usual mental well-being (32.1%) among the 1,074 individuals in the Chinese province of Hubei who answered the online questionnaire.…”
Section: Mental Disorders and Symptoms Associated With Covid-19mentioning
confidence: 99%
“…Corr, P.J. (28) The study suggested that the participants were experiencing psychological conflict: between the urge to stay safe (FFFF-related) and the desire to maintain a normal, pleasurable (RR-related) life. Forms of ameliorating conflict can sometimes include maladaptive behaviors (panic buying), reflecting rewardrelated displacement activity.…”
Section: Bacon Ammentioning
confidence: 99%